Penguatan Nilai Karakter Disiplin Berbasis Budaya Sekolah di Sekolah Dasar - Irwan, Irwan; Suarti, Suarti; Faslia, Faslia; Tarno, Tarno; Gawise, Gawise; Agustien, Stevani (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the strengthening of discipline character values ​​based on school culture in grade V students of SD Negeri 1 Katobengke. This study uses a qualitative descriptive method with data collection techniques including interviews, observations, and documentation. The data analysis techniques used in this study are (1) data collection, (2) data reduction, (3) data presentation, (4) drawing conclusions and verification. The results of the study indicate that strengthening the character values ​​of discipline through school culture at SD Negeri 1 Katobengke is carried out through four activities, namely through routine activities, spontaneous actions, role models and environmental conditioning. Strengthening the character values ​​of discipline through routine morning assembly activities, spontaneous actions carried out, namely reprimanding students who violate school rules, role models that are exemplified by arriving on time, collecting assignments according to the agreed time and appearing neat and environmental conditioning that is applied, namely the existence of school regulations and displays about discipline slogans.